2022
DOI: 10.3390/ijerph19148857
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Physical Activity Behavior by Individuals with Prediabetes and Diabetes during the COVID-19 Pandemic after Completing an Exercise Intervention in Brazil

Abstract: This cross-sectional study evaluated the perception of individuals with prediabetes/diabetes about their living conditions during the COVID-19 pandemic to identify the facilitators, barriers, and reasons to remain physically active at home and adhere to recommended exercise. It included individuals with prediabetes/diabetes who had completed an exercise intervention, which started on-site and moved to a remote home-based regime due to the COVID-19 pandemic and were advised to keep exercising at home. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent systematic review found that home exercise programs were inferior to structured exercise programs in people with intermittent claudication, unless monitoring was included (Pymer et al 2021). A crosssectional study of individuals with prediabetes/diabetes who had completed an exercise intervention which started on-site and moved to a remote home-based regime due to the COVID-19 pandemic, found that only 53.8% adhered to the recommended exercise at home (Ponciano et al 2022). Our findings highlighted that many clients did not actively complete their home exercise program during lockdown, nor did they recall engaging with their exercise group leader via phone.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that home exercise programs were inferior to structured exercise programs in people with intermittent claudication, unless monitoring was included (Pymer et al 2021). A crosssectional study of individuals with prediabetes/diabetes who had completed an exercise intervention which started on-site and moved to a remote home-based regime due to the COVID-19 pandemic, found that only 53.8% adhered to the recommended exercise at home (Ponciano et al 2022). Our findings highlighted that many clients did not actively complete their home exercise program during lockdown, nor did they recall engaging with their exercise group leader via phone.…”
Section: Discussionmentioning
confidence: 99%